Portugal : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Portugal. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights that the economic recovery in Portugal is losing momentum. The slowdown in economic activity that began in the second half of 2015 has persisted, despite still-favorable cyclical tailwinds and supportive macroeconomic policy. The fiscal loosening in place since 2015 and the European Central Bank's appropriately supportive monetary policy stance have translated into robust consumption growth. However, overall GDP growth is being held back by weaker export growth and sluggish investment, with the latter being weighed down by uncertainty, high levels of corporate debt, and still-pronounced structural bottlenecks. Output is expected to increase by only 1.0 percent in 2016.